2020
DOI: 10.17161/eurojecol.v6i1.13520
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife assessment of the Chandragiri hills, Kathmandu: Potentiality for ecotourism

Abstract: Wildlife assessments can provide crucial information regarding species richness, relative abundance and spatial, temporal, and ecological information on wildlife habitat associations. The assessment’s information can in turn be used for developing management policies including for establishing touristic zones. We investigated wildlife occurrences in the Chandragiri Hills, Kathmandu Nepal from 2015-2019 to provide baseline data to inform the potential sites for ecotourism. During the study period, we recorded 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The chances of encountering additional species with increased sampling effort might be attributed to the short isolation distance of the TU area from the Chandragiri Forest, a potential regional species pool in the Kathmandu Valley. The Chandragiri Forest, a natural forest fragment of 11 km 2 is located about 1.4 km away from the TU area and harbors 199 bird species (Katuwal et al, 2020), including almost all species found in our study area. Studies have revealed that bird richness and abundance of small urban parks and greenspaces are greatly affected by isolation distance from local and regional species pools (Fernández-Juricic, 2000;Wang et al, 2013;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The chances of encountering additional species with increased sampling effort might be attributed to the short isolation distance of the TU area from the Chandragiri Forest, a potential regional species pool in the Kathmandu Valley. The Chandragiri Forest, a natural forest fragment of 11 km 2 is located about 1.4 km away from the TU area and harbors 199 bird species (Katuwal et al, 2020), including almost all species found in our study area. Studies have revealed that bird richness and abundance of small urban parks and greenspaces are greatly affected by isolation distance from local and regional species pools (Fernández-Juricic, 2000;Wang et al, 2013;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…1 ). The Suryabinayak community forest is a contiguous forest patch in the southern outskirts of the Kathmandu Valley, and many wild carnivores like leopards, civets, martens and small felids can be found to occur in the forested hills [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…We chose a densely populated locality in the Bhaktapur district that is adjoined by the Suryabinayak community forest on south (Figure 1). The Suryabinayak community forest is a contiguous forest patch in the southern outskirts of the Kathmandu Valley, and many wild carnivores like leopards, civets, martens and small felids can be found to occur in the forested hills [14]. We sampled free-ranging stray dogs in a dense settlement area in central Bhaktapur and used a stratified sampling scheme to collect a proportional number of samples from all parts of the region.…”
Section: Methodsmentioning
confidence: 99%